Characterization of crude extract prepared from Indian curd and its potential as a biopreservative. (June 2021) - Das, Annada; Chauhan, Geeta; Agrawal, Ravi K; Das, Arun K; Tomar, Serlene; Uddin, Siraj; Satyaprakash, Kaushik; Pateiro, Mirian; Lorenzo, José M
The adverse effects of chemical preservatives used to prevent food spoilage have led to the search for various biopreservatives. Considering this, a study was undertaken to prepare crude extract (CE) from Indian curd (a fermented dairy product) and characterized it in terms of antioxidant and antimicrobial activities against some common food-borne bacteria. The CE exhibited well pronounced antimicrobial activity against Bacillus cereus and Salmonella typhimurium . The minimum inhibitory concentration (MIC) of CE was recorded for 2-fold concentrated solution prepared from a 10-fold stock. The CE exhibited a significantly higher ( p < 0.05) antioxidant and antimicrobial activities compared to its fractions. The CE was found to be heat stable (up to 100 ℃ for 30 min) and exhibited a significant ( p < 0.05) increase in activity at pH 2–7 and in combination with 2% citric acid solution. Trypsin treatment suggested it to be of proteinaceous in nature. The antibacterial activity of CE remained intact at 4 ℃ for seven days, whereas non-significant ( p > 0.05) changes in its activity were noted during storage at −20 ℃ for 30 days. The curd sample used for preparation of CE, when tested for bacteriocin production and subsequent antimicrobial activity, did not show inhibition against S. typhimurium . Sodium dodecyl sulphate-polyacrylamide gel electrophoresis analysis of CE and its fractions revealed multi-banding pattern. By virtue of its bioactivities observed, CE can be explored as a promising food biopreservative.